2021
DOI: 10.7150/ijms.59185
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Study of Antitumour Immunotherapy for Newcastle Disease Virus

Abstract: This article reviews the preclinical research, clinical application and development of Newcastle disease virus (NDV) in the field of cancer therapy. Based on the distinctive antitumour properties of NDV and its positive interaction with the patient's immune system, this biologic could be considered a major breakthrough in cancer treatment. On one hand, NDV infection creates an inflammatory environment in the tumour microenvironment, which can directly activate NK cells, monocytes, macrophages and dendritic cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 91 publications
(89 reference statements)
0
20
0
Order By: Relevance
“…The following approaches were used to apply NDV for cancer treatment: NDV oncolysate vaccines [ 124 , 125 , 126 ]; autologous tumor cell vaccine (ATV-NDV) [ 127 , 128 , 129 ]; oncolytic NDV alone and in combination with durvalumab (NCT03889275, NCT04613492) [ 130 , 131 ]. …”
Section: Oncolytic Viruses In Clinical Trialsmentioning
confidence: 99%
“…The following approaches were used to apply NDV for cancer treatment: NDV oncolysate vaccines [ 124 , 125 , 126 ]; autologous tumor cell vaccine (ATV-NDV) [ 127 , 128 , 129 ]; oncolytic NDV alone and in combination with durvalumab (NCT03889275, NCT04613492) [ 130 , 131 ]. …”
Section: Oncolytic Viruses In Clinical Trialsmentioning
confidence: 99%
“…At times of personalized and individualized medicine the concept of randomizedcontrolled clinical trials (RCTs) as exerted by big pharma companies in the last decades is being questioned and should be further discussed [166]. A comparative analysis of the side effects of systemic therapies revealed that cancer vaccines and OVs exert profoundly lower side effects than agents such as cytostatic drugs and SMIs [167]. The aspect of side effects, such as major adverse events (WHO grades 3-4) should in future be considered more seriously in the evaluation of RCTs [167].…”
Section: Future Directionsmentioning
confidence: 99%
“…Lentogenic strains, such as LaSota or B1, show the lowest virulence in chicken [ 1 ] and have an extensive documented history of being safe in humans, as has been shown in clinical trials using NDV as an oncolytic agent [ 34 , 35 ]. More detailed information on such trials can be found in the most recent reviews on the oncolytic application of NDV [ 17 , 36 , 37 ]. Mesogenic and velogenic strains, on the other hand, are typically not used as vaccine vectors due to their virulence in chicken [ 1 ] and their status as a “Select Agent” in the United States [ 13 ].…”
Section: Characteristics Of Ndv As a Viral Vectormentioning
confidence: 99%